BIOFILM FORMATON POTENTIAL OF BACTERIA RECOVERED FROM WATER TAPS AND SINKS - Adebajo, Seun; Ariom, Thaddeus; Ike, Williams; Akintokun, Aderonke (FUDMA Journal of Sciences, 2026)
Biofilms are bacterial communities embedded in a polysaccharide matrix, resistant to antibiotics, environmental stress, biocides and could cause increase in the prevalence of diseases worldwide. This study elucidates the biofilm forming abilities of bacterial isolates from water taps and sinks. Water taps and sinks swabs samples were collected from Federal University of Agriculture, Abeokuta (FUNAAB), Isolu, Oshiele and Federal Medical Centre (FMC), Abeokuta. Isolation and identification of bacteria were carried out using standard microbiological methods and tube method was employed for biofilms assay. The isolated bacteria species include Escherichia, Klebsiella, Salmonella, Proteus, Pseudomonas and Citrobacter. The highest bacterial count of 9.8×105(cfu/mL) was obtained from Oshiele tap samples while the lowest count was gotten from FMC sink samples (1.2×105cfu/mL). Out of 108 bacteria isolated, 36 bacteria were biofilm formers. The isolated bacteria from FUNAAB hostel tap exhibited the highest biofilm potential followed by OSHIELE samples while FMC sink samples had highest bacteria biofilms. This study, thus, revealed that bacterial biofilm formers could be found in taps and sinks and presence of these diverse bacterial biofilms in the tap outlets and sinks could pose a serious threat to life-forms.